Survey Penerapan Strategi Problem Based Learning (PBL) di SMK Teknologi dan Rekayasa Selama Masa Pandemic Covid-19 - Rusmono Rusmono (Peneliti.net, 2021)
This study aims to determine the factors that support and hinder the implementation of PBL strategies in online learning in technology and engineering vocational schools during the COVID-19 pandemic. The research method used was a cross sectional survey (Lavrakas, 2008) to draw conclusions about the population of interest (teachers of SMK Negeri 39 Central Jakarta) at one point in time. A total of 12 lecturers of the TAV and TEI expertise programs aged 30 to 53 filled out the questionnaire. The results showed that the supporting factors for implementing the PBL strategy were self-confidence in professional development; understanding of PBL concepts; School management support; and teachers' perceptions of the school environment. Meanwhile, the constraint factors for implementing PBL strategies are lack of confidence in professional development; the notion that it is not important to implement a PBL strategy that can improve performance; and there is no specific guideline for PBL strategy. The findings in this study are the need to strengthen pedagogical competencies, especially in the implementation of PBL strategies, and develop a PBL Strategy Guidebook at SMKN 39 Jakarta.